School as a Social System - Kıvanç Bozkuş (Sakarya University Journal of Education)
Social system notion which belongs to the systems theory has been elaborated comprehensively using its founders' ideas, and characteristics of schools have been explained consulting to this notion. The course of social system idea has been reviewed along with its relation to other systems. How researchers who assumes schools as social systems define the main components of the school has been reviewed.